Analysis of Optical Erasure Efficiency in WDM-PONs Employing Carrier Remodulation. Issue 4 (4th July 2018) - Batalha, Camilla de Santana; Duarte, Ulysses Rondina; Martinez, Maria Aparecida Gonçalves; Romero, Murilo A.
ABSTRACT: This paper proposes a method to monitor the operation performance of reflective semiconductor optical amplifier (RSOA)-based optical network units (ONUs) in wavelength-reuse wavelength-division-multiplexing passive optical network topologies. For this goal, the optical erasure efficiency of ONU RSOA is numerically evaluated through remote measurements at the optical line terminal site, using the VPI Transmission Maker software. The results show good correlation with the optical erasure behavior of RSOA in the injection power range of –20 to –5 dB, bias current of 50 and 150 mA, and confinement factor of 0.2 and 0.3. As a consequence, this method can be used to qualitatively estimate the optical and electrical features of ONU RSOA from the central office, instead of performing a local direct measurement.